Penguatan Keterlibatan Warga Negara berupa Political Voice dan Civic Activity melalui Komunitas Kewarganegaraan - Pradana, Yudha; Cecep Darmawan; Rahmat; Leni Anggraeni (Universitas Negeri Semarang, 2025)
This study aims to reveal how reflection on empowering civic communities serves as a forum for strengthening civic engagement, particularly in the realms of political voice and civic activity. Civic engagement is a significant aspect of the discourse on cultivating smart and good citizen, especially given the technological advances that can optimize widely recognized and accessible digital platforms. This study employs a phenomenological method with a qualitative approach to explore the reflections of civic communities on enhancing civic engagement. Data collection involves interviews and documentation studies, with data analysis conducted using Atlas.ti. The results indicate that strengthening civic engagement through civic communities is grounded in the community's vision and movement patterns, particularly by leveraging digital platforms. For instance, the Bareng Warga Community uses change.org to conduct online petitions as a form of political voice, while the Nusa Bumi Lestari Community utilizes kitabisa.com for crowdfunding as a form of civic activity. Additionally, the collaboration and networking among civic communities play a crucial role in reinforcing civic engagement, enabling citizens to be dedicated and committed to achieving the common good.